An Empirical Study of Small Retail Investors in India on Investors' Perception of Investing in the Stock Market - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana; Devi, Takhelchangbam Brajeshwari; Devi, Shoraisam Kiranbhala; Singh, Shoraisam Kiran (Integrated Journal for Research in Arts and Humanities, 2022)
The perception of investors depends on the different behavioral traits. The stock market seems to be an exciting and exciting platform for investors to perform their investment activities (frydrych et al., 2014). The market has continuously grown over time in these years. However, investors are sometimes skeptical about investing because of the uncertainties and risks associated with the stock market. After going through many hurdles, the money earned over a long time is meant to be safe and risk-free. Therefore, the investors feel the risk in the stock market is high and fear investing in platforms like these. Awareness of the stock market is also essential for investing in suitable firms. There must be a fair understanding of the return on investments (roi) before investing a large sum of money into the firms (farris et al., 2015). As this is a hot topic among businesses, the study of the behavior of small investors concerning the stock market must be carried out to understand their perspective. Financial behavior is an important concept to understand if one wishes to analyze the perception of individual investors. It has been observed that some of the investors are dependent on self-made decisions while investing, whereas some are made aware by the different financial seminars or workshops. Therefore, this paper deals with empirical findings to establish a more profound understanding of the behavior of investors following the stock market. A sample of 117 small retail investors was surveyed through a structured questionnaire to know their perception of investing in the stock market and its impact on the investment process in India. The study concludes that there is a significant impact on investors' perception of investing in the stock market.